Relevansi Kebijakan Fiskal pada Masa Rasulullah dan Utsman Bin Affan di Indonesia - Rizki Ramdani Akbar; Sonia Oktafiani; Niken Putri Ayu; Faisal Hidayat; Miftahur rahmah (Universitas Islam Darul 'ulum Lamongan, 2024)
Islamic economics is an economic system based on sharia rules and the main legal references are the Qur'an and Sunnah. This system is constantly evolving. Sharia tax policies have existed since the time of the Prophet SAW. The profit-sharing mechanism for the Islamic State is fay', ghanima, kharaj, jizyah, ushur and khums, just like during the time of Caliph Ustman bin Affan. The purpose of this study is to reveal the Islamic economics in the Uthman bin Affan period. The research method used is library research. The results of the study show that the form of Islamic economics in the era of Ustman bin Affan (644-656) can be derived from the policies of zakat, kharaj, jizyah and price control.